Vortical flow behind isolated helicopter fuselage - Batrakov, A.S.; Kusyumov, A.N.; Mikhailov, S.A.; Garipova, L.I.; Barakos, G.N. (My University, 2014)
This paper present a Computational Fluid Dynamics study of the flow structures behind a helicopter fuselage. Helicopters, in general, are not as streamlined as fixed-wing aircraft and their fuselages may have large areas of flow stagnation as well as rear-facing surfaces with suction and flow separation. Further complications with this flow arise from the possibility of the flow to be unsteady if the separation region becomes large. After validation against experiments, the Computational Fluid Dynamics results are used to study the structure and flow topology behind a realistic helicopter fuselage. It is evident that relatively small details of the geometry can have significant effect on the flow structures and the resulting drag.